Unraveling the interplay of leadership, collaboration, and innovation in the public sector: an analytical exploration through innovation capability and ambidexterity - Picavet, Marc Eric Barda (2023)
This thesis consists of three articles that contribute to the public administration literature on innovation and its intersection with leadership and collaboration. Central to this exploration is the concept of innovation capability. In this regard, the first article, entitled "Understanding Innovation Capability in the Public Sector: A Research Agenda," conducts a systematic review of the literature, proposes a comprehensive definition of innovation capability in the public sector, identifies common themes, and identifies gaps for future research. One of the key contributions of this paper is the identification of a significant gap in the innovation capability literature, which focuses predominantly on the private sector and overlooks the distinctive characteristics of the public sector, such as public value and political leadership. In light of this gap, the second article titled "Advancing Innovation Capability in the Public Sector: The Enabling Role of Mayors' Political Leadership," focuses on mayor’s political leadership and its impact on innovation capability. This idea is explored through two case studies: an urban forestry plan in Palmas, Brazil, and a solid waste management initiative in Gangtok, India. The findings led to the development of four propositions: mayors can enable innovation capability by incorporating external knowledge, by promoting collaboration, by mobilizing financial resources, and by actively supporting innovation. However, to be effective support and commitment from mayors is crucial. Finally, in the third article, titled "Exploring the Link between Top Leadership Style and Ambidexterity in Innovative Public Collaborations", the focus shifts to another concept linking innovation, leadership, and collaboration, which has been relatively underexplored in the public sector: ambidexterity. In this regard, to investigate the links between top leadership and ambidexterity in innovative public collaborations, a case on urban agriculture in the city of Florianopolis, Brazil, was analyzed. The results show that a transformational leadership style was associated with exploratory innovation, while a transactional leadership style was associated with exploitative innovation. These initial findings highlight the importance of combining different top leadership styles, whether through shared leadership or rotational leadership, to enhance ambidexterity and improve innovation in public collaborations. The results of the three articles not only contribute to the existing body of knowledge, but also lay the foundation for future research in this area.